How GNNs Can Be Used in the Vehicle Industry - Granado, Felipe Macías; Alkhaled, Lama (Artificial Intelligence and Applications, 2025)
Graph neural networks (GNNs) have garnered substantial interest across different fields, including the automotive sector, owing to their adeptness in comprehending and managing data characterized by intricate connections and arrangements. Within the automotive realm, GNNs can be harnessed in diverse capacities to elevate effectiveness, safety, and overall operational excellence. This study is centered on the assessment of various GNN models and their potential performance within the automotive sector, utilizing widely recognized datasets. The objective of the study was to raise awareness among researchers and developers working on vehicle intelligence systems (VIS) about the potential benefits of utilizing GNNs. This could offer solutions to various challenges in this field, including comprehending complex scenes, managing diverse data from multiple sources, adapting to dynamic situations, and more. The research explores three distinct GNN models named ViG, point-GNN, and few-shot GNN. These models were evaluated using datasets such as KITTI, Mini Imagenet, and ILSVRC. Received: 18 August 2023 | Revised: 23 November 2023 | Accepted: 5 January 2024 Conflicts of Interest The authors declare that they have no conflicts of interest to this work. Data Availability Statement Data sharing is not applicable to this article as no new data were created or analyzed in this study. Author Contribution Statement Felipe Macías Granado: Conceptualization, Methodology, Software, Validation, Formal analysis, Investigation, Data curation, Writing - original draft, Visualization. Lama Alkhaled: Writing - review & editing, Visualization.